Histological disease activity in patients with microscopic colitis is not related to clinical disease activity or long‐term prognosis. Issue 1 (21st May 2021) - Olsen, Lærke Müller; Engel, Peter Johan Heiberg; Goudkade, Danny; Villanacci, Vincenzo; Thagaard, Jeppe; Walbech, Julie Sparholt; Bohr, Johan; Kupcinskas, Juozas; Verhaegh, Bas; Münch, Andreas; Guagnozzi, Danila; Fernández‐Bañares, Fernando; et al.
Summary: Background: Microscopic colitis (MC) is a common cause of chronic watery diarrhea. Biopsies with characteristic histological features are crucial for establishing the diagnosis. The two main subtypes are collagenous colitis (CC) and lymphocytic colitis (LC) but incomplete forms exist. The disease course remains unpredictable varying from spontaneous remission to a relapsing course. Aim: To identify possible histological predictors of course of disease. Methods: Sixty patients from the European prospective MC registry (PRO‐MC Collaboration) were included. Digitised histological slides stained with CD3 and Van Gieson were available for all patients. Total cell density and proportion of CD3 positive lymphocytes in lamina propria and surface epithelium were estimated by automated image analysis, and measurement of the subepithelial collagenous band was performed. Histopathological features were correlated to the number of daily stools and daily watery stools at time of endoscopy and at baseline as well as the clinical disease course (quiescent, achieved remission after treatment, relapsing or chronic active) at 1‐year follow‐up. Results: Neither total cell density in lamina propria, proportion of CD3 positive lymphocytes in lamina propria or surface epithelium, or thickness of collagenous band showed significant correlation to the number of daily stools or daily watery stools at any point of time. None of the assessed histological parameters at initial diagnosis were able to predict clinical disease course at 1‐year follow‐up. Conclusions: Our data indicate that the evaluated histological parameters were neither markers of disease activity at the time of diagnosis nor predictors of disease course. Abstract : The histopathological parameters total cell density in lamina propria, proportion of CD3 positive lymphocytes in lamina propria and surface epithelium, and thickness of collagenous band did not correlate to the number of daily stools or daily watery stools at time of diagnosis nor predict clinical disease course at 1‐year follow‐up.